The effect of sample preparation parameters on magnetoresistance ratios (MR%) in CO/CU nanostructures - Lau, Yee Chen (2005)
The research reported in this thesis is primarily aimed at establishing the fundamental understanding of magnetoresistance (MR) phenomena occurring in layered magnetic nanostructures of Co/Cu system fabricated using sputtering and electron beam method. Emphasis is given on the studies of magnetoresistance ratios (MR%) as functions of Co layer thickness, working pressure, annealing time and temperature, number of bilayer, direction of magnetic fields, and the application of buffer layer. The Co/Cu/Co sandwiches in this study were fabricated on corning glass substrates. The electrical resistance of samples was measured using the four point Van der Pauw method when magnetic fields of Â± 2500 gauss were applied. It was observed that, the MR% attained almost 10% between 2 - 6 nm of the Co layer thickness. By varying the working pressure, a maximum MR% of 11.4% was obtained at a working pressure of 2.6 x 10-3 torr. In the other hand, the MR% also increases with the increasing of annealing temperature and time. In the bilayers number, n various MR% was revealed by the existence of up-down fluctuations with the MRâ€™s peak and valley occurring at n = 5 and n = 8, respectively. It was also observed that, the magnetic field applied in plane to the samples with and without chromium buffer layer produced higher value MR% of compared to those applied perpendicularly. Thus, the results indicate the dependent of MR% on various preparation parameters.